Taxonomic Inventory of Hardwood Trees (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Hardwood plants play a crucial role in maintaining ecological balance and providing a habitat for various species. Understanding the biodiversity of hardwood plants is essential for conservation efforts and sustainable management practices. Union Christian College serves as a unique location to study the diversity of hardwood plants due to its varied ecosystems and geographical location. A taxonomic inventory of hardwood plants was conducted in Union Christian College to explore the biodiversity of hardwood plants. Documentation was conducted to identify and collect data on the different species of hardwood plants. Information on the scientific name, common name, local name, and frequency was recorded. Their conservation status was also determined using the catalog of Department of Environment and Natural Resources (DENR) Administrative Order 2007-001. The findings revealed that the school houses six hardwood plants. One of the most important trees within this locale is the pair of Velvet Apple Trees or Mabolo (Diospyros blancoi). These trees are particularly fascinating due to their rarity, as they are endemic to the Philippines, are categorized as critically endangered, and that they thrive in an urban area, right at the heart of the city where the school is situated. The existence of four Narra trees (Pterocarpus indicus) in UCC which are also critically endangered. Other hardwood trees include one Governor’s Plum Tree or Seriales (Flacourtia indica), three Mango trees (Mangifera indica), one Madre de Cacao (Gliricidia sepium), and one Jackfruit tree or Langka (Artocarpus heterophyllus). These trees are not vulnerable species, but still requires proper care and conservation. The results of this study provide valuable insights into the taxonomy and status of hardwood plant species growing in an urban location. Understanding the status of these plants not only enhances the knowledge of plant diversity in an area but also contributes to its conservation efforts. Further research on the distribution and ecology of hardwood plants in this area can help inform conservation strategies and ensure the preservation of these valuable plant species.
Keywords: Hardwood